Application of the Codeigniter Framework and Webservice on the Application for Personnel Information at the University of Muhammadiyah Bengkulu - Adnan Fadillah; Khairullah Khairullah (Penerbit Jurnal Indonesia, 2021)
Utilization of technology has been widely used in various fields, namely education, government agencies, banking, trade, industry, and national defense in meeting the needs of their work activities. an organization that meets the needs of daily transaction processing, supports operations, is managerial and strategic activities of an organization, and provides certain outside parties with the necessary reports. University of Muhammadiyah Bengkulu, already has a website-based personnel information system. so the author tries to develop from 2 aspects. Where is the first aspect on the server, the author tries to develop a server application using codeigniter combined with AJAX so that it is easier to connect it with JSON encode. The purpose of this study is to provide information on employees and lecturers at the University of Muhammadiyah Bengkulu which can help the personnel department provide information more quickly and efficiently. It is hoped that the development of this application can be a reference not only for the world of university staffing but also for all subjects and all circles as the development of information technology..